Transformational leadership: an examination of South Kalimantan School Principals' Leadership Style - perdana, iwan; Binti Ishak, Rosnah; binti Mansor, Mahaliza (Jurnal Edusci, 2024)
The headmaster plays a crucial part in ensuring the school's advancement and caliber. transformational school leaders are crucial in advancing educational innovation and Restructuring. The survey was designed to get information on their opinions regarding the practice of transformational school leadership. 335 teachers at private schools who participated in this study were chosen freely due to the wide distribution of the population in South Kalimantan, as demonstrated by their willingness to complete an online survey via Google Forms. The questionnaire is used to measure transformational leadership and builds on Bass's theory (1985). It is clear from the results that transformational leadership fell into the high category. Individualized consideration, intellectual stimulation, inspirational drive, and idealized influence are all high categories, as demonstrated by the four components outlined by Bass (1985).